The Involvement of GAS6 Signaling in the Development of Obesity and Associated Inflammation - Kuo-Sheng Wu; Yi-Jen Hung; Chien-Hsing Lee; Fone-Ching Hsiao; Po-Shiuan Hsieh (International Journal of Endocrinology)
Growth arrest-specific 6 (GAS6), a vitamin K-dependent protein, plays a role in the survival, proliferation, migration, differentiation, adhesion, and apoptosis of cells. GAS6 is highly expressed during growth arrest, followed by a sharp decrease during differentiation in adipocytes. The functions of GAS6 signaling are limited to TAM (Tyro3, Axl, and Mer) receptors and are dependent on the cell type. While many studies have focused on the role of GAS6 in inflammation and cancer, only few studies focused on its roles of GAS6 in obesity. Accordingly, the participation of GAS6 in the progression of obesity remains controversial. In this review, we summarize the results of current studies from clinical and basic research to elucidate the possible role of GAS6 signaling in obesity and associated disorders. In addition, this summary may offer a direction to develop clinical therapeutic strategies for the prevention and treatment of obesity and related complications.